Annexin A5 in treated hypertensive patients and its association with target organ damage. Issue 1 (January 2017) - Maloberti, Alessandro; Meani, Paolo; Vallerio, Paola; Varrenti, Marisa; Casadei, Francesca; Musca, Francesco; Facchetti, Rita; Di Blasio, Anna M.; Ravassa, Susanna; Mancia, Giuseppe; Giannattasio, Cristina
Abstract : Objective: Annexin A5 (AnxA5) has been previously linked to the presence of carotid and cardiac target organ damage (TOD) in the context of heart failure and rheumatologic patients. However, information is scant in the context of hypertension. Aim of our study was to evaluate AnxA5 in treated hypertension patients compared with normotensive controls and to determine whether it is associated with vascular and heart TOD evaluated as arterial stiffness, carotid plaque and left ventricular hypertrophy. Methods: We enrolled 123 consecutive treated hypertension and 124 normotensive controls. TOD was evaluated as pulse wave velocity (PWV, complior), left ventricular hypertrophy (echocardiography) and intima–media thickness and carotid plaque presence (ecographic methods). AnxA5 levels was dosed and compared in patients with and without hypertension and with and without TOD. Results: With similar age hypertension patients showed higher SBP, DBP and AnxA5 levels (13.9 ± 11.1 vs 10.1 ± 8.4 ng/ml, P  < 0.001) compared with controls. Regarding TOD hypertension showed higher PWV (8.5 ± 1.8 vs 7.6 ± 1.5 m/s, P  < 0.001) and LVMI (121.7 ± 29.3 vs 113.5 ± 21.1 g/m 2, P  < 0.05), whereas carotid intima–media thickness was superimposable. AnxA5 correlates with PWV ( r  = 0.13, P  < 0.05) and DBP (r = 0.15, P  < 0.01), whereas it has never been found as a significant independent predictor of TOD in linear regression analysis. Conclusion: Our data have shown that AnxA5 levels are increased in treated hypertension patients. In this condition, it is probably released in the plasma as a defensive mechanism through its anti-inflammatory and anticoagulants effects. We found a significant association with arterial stiffness, but AnxA5 was not found to be a significant predictor of TOD.